ChemInform Abstract: Palladium‐Catalyzed Intramolecular Reductive Cross‐Coupling of Csp2—Csp3 Bond Formation. Issue 3 (January 2015) - Liu, Hui; Wei, Jianpeng; Qiao, Zongjun; Fu, Yana; Jiang, Xuefeng
Abstract An efficient Pd‐catalyzed reductive intramolecular cross‐coupling of bis‐iodo substrates of type (I) is developed to give good yields of indolines (II).